Interior of the ancient Chapel of St. Mary Magdalene, Guildhall - Jones, G.; Springsguth, M. (Tufts Archival Research Center, 2008)
Interior of the Chapel when used as a Court of Requests, looking east. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.